Vasculopathic Cranial Ocular Motor Neuropathy Following Sudden Emotional Stress - Purvin, Valerie (Frontiers in Neurology, 2010)
We describe 3 patients who experienced onset of a microvascular ocular motor nerve palsy in the setting of sudden emotional stress. Such emotional states are accompanied by a marked increase in sympathetic tone in some individuals. Mechanisms by which these autonomic changes might produce an ischemic cranial nerve palsy include intra-cranial vasoconstriction and transient systemic hypotension due to alterations in cardiac function.